Colour and Escape Behaviour in Polymorphic Populations of an Aposematic Poison Frog. (29th May 2015) - Dugas, Matthew B.; Halbrook, Susannah R.; Killius, Allison M.; del Sol, Jillian F.; Richards‐Zawacki, Corinne L.; Koenig, W.
Abstract The phenomenon of aposematism, or the pairing of antipredator defence with conspicuous or distinctive signals, serves as an excellent example of how traits act in concert to shape fitness. Not only does this complex phenotype require the integration of multiple traits, it alters the fitness pay‐offs of yet others. The protection offered by aposematism may, for example, reduce the costs associated with foraging or sexual display. Thus, well‐protected aposematic lineages should be bolder, more active and less likely to respond to perceived threats of predation than more cryptic lineages. Comparisons of differently coloured morphs of the polytypic strawberry poison frog (Oophaga pumilio) have supported the predicted behavioural correlates of aposematism, with the exception of those regarding responsiveness to simulated predators. We tested the key prediction that aposematic coloration will be associated with reduced sensitivity to predators in two polymorphic O. pumilio populations. The novel approach of studying polymorphic populations allowed us to assess the effect of colour in the absence of potentially confounding habitat differences. We found that colour was associated with the probability that a frog would attempt escape and the distance at which it fled, but only in one population, and not in the predicted direction. An overall comparison of the two populations superficially supported our predictions, but this pattern actually arose because frogs occupying higher perches were less likely to respond, a pattern that may reflect the value of high perches and the costs associated with returning to them after attempted escape. These results highlight the complexity of the relationship between predators and prey, the challenges associated with understanding how and why traits are correlated, and the intimate ties between behaviour and morphological evolution.